Adaptive direction-guided structure tensor total variation - Demircan-Tureyen, Ezgi; Kamasak, Mustafa E. (Elsevier BV, 2021)
Direction-guided structure tensor total variation (DSTV) is a recently proposed regularization term that aims at increasing the sensitivity of the structure tensor total variation (STV) to the changes towards a predetermined direction. Despite of the plausible results obtained on the uni-directional images, the DSTV model is not applicable to the multi-directional images of real-world. In this study, we build a two-stage framework that brings adaptivity to DSTV. We design an alternative to STV, which encodes the first-order information within a local neighborhood under the guidance of spatially varying directional descriptors (i.e., orientation and the dose of anisotropy). In order to estimate those descriptors, we propose an efficient preprocessor that captures the local geometry based on the structure tensor. Through the extensive experiments, we demonstrate how beneficial the involvement of the directional information in STV is, by comparing the proposed method with the state-of-the-art analysis-based denoising models, both in terms of restoration quality and computational efficiency.

13 pages, 6 figures, article
Keywords: FOS: Computer and information sciences; Inverse Problems; Computer Vision and Pattern Recognition (cs.CV); Directional Total Variation; Image and Video Processing (eess.IV); Computer Science - Computer Vision and Pattern Recognition; FOS: Electrical engineering, electronic engineering, information engineering; Image Denoising; Variational Models; Electrical Engineering and Systems Science - Image and Video Processing